Concise Review of Common Non-Traditional Dyslipidemic Indices in Clinical Practice - Mudhafar Khazaal (AlQalam Journal of Medical and Applied Sciences, 2023)
Lipids are transported a variety of target organs and tissues to be used for the synthesis of steroid hormone, the production and storage of energy, the synthesis of bile, vitamin absorption, signalling molecules in cellular communication. Some unhealthy practices may derange levels of lipid, skewing them away from their individual reference ranges. If any type of lipid gets imbalanced, whether secondary to a chemical defect in lipid pathway handling or to unhealthful practices, a clinical situation called dyslipidemia will ensue. Dyslipidemia is a risk factor for the development of cardiovascular adverse events. Traditionally, dyslipidemia identification, as early as possible, reduces cardiovascular events. The screening tools for dyslipidemia are the fasting lipid panel and lipid ratios from which several “atherogenic indices” have been proposed to predict cardiovascular risk. In this article, a quick review of the untraditional dyslipidemic parameters will be explained.